Compudose® implant vs a Ralgro® plus Synovex-S® reimplant program for finishing steers - Laudert, S.; Eder, J.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station, 2011)
Compudose implanted feedlot steers performed similarly to steers initially implanted with Ralgro and reimplanted with Synovex-S. Steers lost 2.9% of the Compudose implants.
Keywords: Beef; Implant; Reimplant; Finishing steers